MIGRASI ROHINGYA: TANTANGAN INTEGRASI SOSIAL DAN EKONOMI DI NEGARA PENERIMA - Cinta Prasasti; Suci Wheli Melvia; Muhammad Irwan Sahruddin Nasution; Ricu Sidiq; Lister Eva Simangunsong; Muhammad Ihsan Syahaf Nasution (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
Rohingya migration has become a complex challenge that requires in-depth understanding and a holistic response from various relevant parties. In this context, this article discusses various aspects that influence the social, economic and ecological integration of Rohingya migrants in receiving countries, with a special focus on Indonesia. The research method used is a qualitative approach with descriptive methods to explore the phenomenon of Rohingya migration and the challenges of social and economic integration in receiving countries. The descriptive method was chosen because the focus of this research is to describe and explain complex situations from an in-depth and comprehensive perspective. The data collected in this research is descriptive, including words, images and information from various sources, such as books, scientific journals and previous research that are relevant to the topic under study. The results of this research show that there are several main challenges faced by Rohingya migrants, including limited access to education, health services and employment, as well as social discrimination and stigmatization. Apart from that, unclear legal status, cultural and religious differences, as well as political and humanitarian instability also affect their integration process. In addition, this article also describes the environmental impacts of Rohingya migration and the importance of considering ecological factors in natural resource management and infrastructure development. To address these challenges, cross-sectoral and cross-institutional collaboration is key, with a focus on inclusive approaches, human rights protection and environmental sustainability. Diplomatic efforts are also important in resolving the root causes of the Rohingya crisis in their home country. With strong cooperation and commitment to holistic solutions, Indonesia has the potential to be a leader in responding to the challenges of social, economic and ecological integration in the context of Rohingya migration.